A Dominant Caste and Political Violence: A Sociological Study on Factionalism in Rayalaseema - Dandu, Chinna Rangaiah; Shaik, Nyamath Hussain (South India Journal of Social Sciences, 2025)
The Rayalaseema region, situated in Andhra Pradesh, India, has historically been marked by factional violence, and various political leaders have strategically utilised it to advance their political objectives. Factionalism is a phenomenon that is particularly pronounced in the districts of Kadapa, Kurnool, and Anantapur. In these locales, political leaders have actively engaged with and modified factional dynamics to secure political leverage, resulting in a vehement interrelationship between politics and factionalism within the region. Based on the fieldwork conducted in Sambaturu village from March to May 2018, the snowball sampling technique and secondary data, the present study investigates the dynamics of factionalism and its intersection with politics in a village within the Kadapa district of Rayalaseema. With the objective of exploring and analysing the sociological dimensions of factionalism and political interactions within this specific context, the study finds that factionalism is intricately associated with caste, class, and gender, and it metamorphoses into a new form of feudal setup with the nexus with State.